Pengaruh Pemanfaatan Video Pembelajaran Terhadap Hasil Belajar Pada Mata Pelajaran Ekonomi Kelas XI IPS - Dewi, Kadek Puspa; Tripalupi, Lulup Endah (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This study aims to find out the effect of the use of learning videos on learning outcomes. The sample technique used in this study was a saturated sample of 71 students. The data collection method in this study uses test instruments. Data analysis techniques using T test. The results of this study showed that the utilization of learning videos has a positive and significant effect on learning outcomes. The completion value of the learning outcomes in the control class was 19.44% and the completion value of the learning outcomes in the experimental class was 77.14%. There are significant differences in learning outcomes taught by utilizing learning video media and without utilizing learning video media with a significance value of 0.000.